1957
DOI: 10.1152/ajplegacy.1957.189.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Trigemino-Bulbar Reflex Pathways

Abstract: In decerebrate and decerebellate cats stimulation of any division of the trigeminal nerve induces efferent volleys in the VIIth, Xth, XIth and XIIth nerves. Direct stimulation of the face, internal nares and dura mater produces similar volleys. In uncurarized animals similar stimuli cause twitches of face and neck muscles. Slowing of the heart rate may also be induced. Conduction times measured in the brainstem and cranial nerves show that conduction is very rapid in the brainstem to the level of the obex, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

1968
1968
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Developmental studies of human and rat fetuses have demonstrated that perioral stimuli elicit head movements along with oral responses (Humphrey, 1964;Narayanan et al, 1986). Sternocleidomastoid and trapezius contraction can be elicited by direct stimulation of the Gasserian ganglion of the adult cat (Green et al, 1957). Intracellular responses have Received for publication April 26, 1991 Accepted for publication September 8,1993 been elicited in splenius and trapezius motoneurons following stimulation ofboth Vi (supra-orbital nerve) and V2…”
mentioning
confidence: 99%
“…Developmental studies of human and rat fetuses have demonstrated that perioral stimuli elicit head movements along with oral responses (Humphrey, 1964;Narayanan et al, 1986). Sternocleidomastoid and trapezius contraction can be elicited by direct stimulation of the Gasserian ganglion of the adult cat (Green et al, 1957). Intracellular responses have Received for publication April 26, 1991 Accepted for publication September 8,1993 been elicited in splenius and trapezius motoneurons following stimulation ofboth Vi (supra-orbital nerve) and V2…”
mentioning
confidence: 99%
“…Neurons of the three divisions of the cranial nerve V and cranial nerves VII, IX, and X share in the same neuron pool with neurons from the upper cervical segments. [26][27][28] It is well known that trigeminal influences participate in the neuromuscular program during habitual occlusion. 29 Therefore, trigeminal inputs from periodontal, TMJ, and muscular receptors may be playing some role in the modulation of the motor neuron pools of the masseter and sternocleidomastoid muscles when the jaw position varies from intercuspal position to any eccentric jaw posture task.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a closely organized neurophysiological reflex relationship appears to exist between the tonic neck reflex activity and trigeminal reflex activity. [26][27][28][31][32][33][34] From a central neuromechanisms point of view, the influence of the visual system must be considered, because the subjects were asked to keep their eyes open while the EMG recordings were performed. It is well known that this system plays an important role in the perception of head position and in the coordination of eye, head, and neck movements by influencing masseter and sternocleidomastoid muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to provide a measure of the central nervous modulation of cardiac vagal activity, we have examined the net effect on heart rate of the simultaneous application of the trigeminal and muscle heart reflexes. Because the afferent inputs from the two reflexes are anatomically and functionally distinct [47], it can be argued that their combined effects are a consequence of an interaction within the central nervous system. The net effects of simultaneous isometric muscle contraction and trigeminal stimulation on heart rate were significantly greater after β-blocker therapy compared with placebo, indicating a central effect with both β-blockers.…”
Section: A Central or Peripheral Effect Of β-Blockers: Is Lipophilicimentioning
confidence: 99%